2021
DOI: 10.1007/s42452-021-04301-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation: a sustainable environmental technology for heavy metals decontamination

Abstract: Toxic metal contamination of soil is a major environmental hazard. Chemical methods for heavy metal's (HMs) decontamination such as heat treatment, electroremediation, soil replacement, precipitation and chemical leaching are generally very costly and not be applicable to agricultural lands. However, many strategies are being used to restore polluted environments. Among these, phytoremediation is a promising method based on the use of hyper-accumulator plant species that can tolerate high amounts of toxic HMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(119 citation statements)
references
References 209 publications
2
112
0
5
Order By: Relevance
“…The most important heavy metal element to consider in terms of food chain contamination are As, Cd, Hg, Pb and Se, which can disturb human metabolic activities, leading to diseases and even mortality (Rai et al, 2019). However, soil-to-plant metal transfer cannot be predicted solely by the contaminant's chemistry and behavior, as there are other significant processes regulating the aggregation of metals and metalloids in edible parts of vegetables, such as root uptake, root selectivity, ion interactions, rhizosphere processes, leaf uptake from the atmosphere, transpiration rate and plant partitioning (McLaughlin et al, 2011;Nedjimi, 2021). In addition, Biswas et al (2018) reported that environmental related factors such as mineral contents of rainwater and groundwater may also influence the rate of metal uptake by plants.…”
Section: Introductionmentioning
confidence: 99%
“…The most important heavy metal element to consider in terms of food chain contamination are As, Cd, Hg, Pb and Se, which can disturb human metabolic activities, leading to diseases and even mortality (Rai et al, 2019). However, soil-to-plant metal transfer cannot be predicted solely by the contaminant's chemistry and behavior, as there are other significant processes regulating the aggregation of metals and metalloids in edible parts of vegetables, such as root uptake, root selectivity, ion interactions, rhizosphere processes, leaf uptake from the atmosphere, transpiration rate and plant partitioning (McLaughlin et al, 2011;Nedjimi, 2021). In addition, Biswas et al (2018) reported that environmental related factors such as mineral contents of rainwater and groundwater may also influence the rate of metal uptake by plants.…”
Section: Introductionmentioning
confidence: 99%
“…It involves the extraction of contaminants from the soil or water with the help of terrestrial/ aquatic plants. The contaminant would be taken up by the roots and translocated to the leaves, which can then be harvested (Nedjimi, 2021). Thus, a fraction of the contaminant can be removed from the soil.…”
Section: Phytoextractionmentioning
confidence: 99%
“…The plants that are chosen for this method are known as 'Hyperaccumulator' plants. Plants that can accumulate more than 0.1% DW of a contaminant are called hyperaccumulators (Nedjimi, 2021). The ideal characteristics of these plants involve greater above-ground biomass, higher growth rate, efficient translocation, and easy to cultivate and harvest.…”
Section: Phytoextractionmentioning
confidence: 99%
“…Phytoremediation is emerging biotechnology that employs plants to extract, transfer, stabilize and/or destroy organic/inorganic pollutants (Yan et al, 2020). Plants that are useful for environmental remediation has four basic attributes, which are accumulation property of shoots, wild root system, rapid growth and easily harvestable (Nedjimi, 2021).…”
Section: Phytoremediationmentioning
confidence: 99%